Feather/Pity: possible ballet as poetic unfolding (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This is a report on a trajectory that includes studies and professional performance at an international level. By addressing the relationship between classical dance, disability and poetics from the occurrence of a stroke. One arrives at the exposition of Possible Ballet, an investigation in the form of a post-doctorate that took practice based research for the methodological bias. A body practice proposal based on the principles of ballet movement in order to arrive at processes of scenic creation through improvisation. The creation of the work Feather/Pity is addressed, which brought up issues found in current authors who write about dance and disability, ballet technique and creation.
Keywords: ballet; disability; creation; dance research